Green Fabrication of Silver Nanoparticles using Euphorbia serpens Kunth Aqueous Extract, Their Characterization, and Investigation of Its In Vitro Antioxidative, Antimicrobial, Insecticidal, and Cytotoxic Activities. - Ahmad, Nisar; Fozia; Jabeen, Musarrat; Haq, Zia Ul; Ahmad, Ijaz; Wahab, Abdul; Islam, Zia Ul; Ullah, Riaz; Bari, Ahmed; Abdel-Daim, Mohamed M.; El-Demerdash, Fatma M.; Khan, Muhammad Yahya (BioMed Research International, 2022)
The silver nanoparticles (AgNPs) were synthesized via green synthesis approach using Euporbia serpens Kunth aqueous extract. The synthesized AgNPs were characterized by UV-visible spectroscopy and Furrier Transformer Infra-Red spectroscopy to justify the reduction and stabilization of AgNPs from its precursors. AgNPs characteristic absorption peak was observed at 420 nm in the UV-visible spectrum. The SEM and TEM analysis demonstrated the spherical shape of the synthesized nanoparticles with particle sizes ranging from 30 nm to 80 nm. FTIR transmission bands at 2920 cm-1, 1639 cm-1, 1410 cm-1, 3290 cm-1, and 1085 cm-1 were attributed to C-H, C=O, C-C, N-H, and C-N functional groups, respectively. XRD peaks could be attributed to (111), (200), (220), and (311) crystalline plane of the faced-centered cube (FCC) crystalline structure of the metallic silver nanoparticles. The AgNPs showed good antibacterial activity against all the tested bacteria at each concentration. The particles were found to be more active against Escherichia coli (E. coli) with 20 ± 06 mm and Salmonella typhi (S. typhi) with 18 ± 0.5 mm zone of inhibition in reference to standard antibiotic amoxicillin with 23 ± 0.3 mm and 20 ± 0.4 mm zone of inhibition, respectively. Moderate antifungal activities were observed against Candida albicans (C. albicans) and Alternaria alternata (A. alternata) with zone of inhibitions 16.5 mm and 15 mm, respectively, compared to the standard with 23 mm of inhibition. Insignificant antifungal inhibition of 7.5 mm was observed against Fusarium gramium (F. gramium). All the tested concentrations of AgNPs showed comparable % RSA with the standard reference ascorbic acid in the range sixty percent to seventy five percent. The percent motility at 3 hours postincubation showed quick response and most Tetramorium caespitum were found deceased or paralyzed. Similarly, the percent mortality showed a linear response at concentration and time. It was observed that 1 μg/mL to 2 μg/mL concentration of AgNPs displayed a significant cytotoxic activity against Artemia salina with LD50 of 5.37 and 5.82, respectively.